Writing fiction - Cassill, R. V. (Ronald Verlin) (Englewood Cliffs, New Jersey : Prentice-Hall, 1975)
Contents: Section One: The mechanics of fiction. 1. Reading as a writer -- 2. Choosing a subject -- 3. Description, narrative passages, scenes, and dialogue -- 4. Finger exercises -- 5. Notebooks and lists. Section two: The stories. In the central blue / R. V. Cassill -- Taking care / Joy Williams -- The lady with the pet dog / Anton Chekhov -- Us he devours / James B. Hall -- Murphy's Xmas / Mark Costello -- The best of everything / Richard Yates. Section Three: The concepts of fiction. 6. Unity -- 7. Plot as unity -- 8. Character -- 9. Tone -- 10. Theme.
Keywords: FICTION -- AUTHORSHIP